Use of alternative dispute resolution technique of mediation for speedy and fair resolution of land use dispute in Malaysia - Maidin, Ainul Jaria (s.n, 2012)
Disputes in land use and environmental areas are on the rise. The courts are struggling to effectively resolve the conflicts. The complexities of land use and environmental disputes are posing challenges to the courts due to multiple parties and issues, technical and scientific complexities, and power imbalances. The traditional method of settling land use, environmental and land development disputes through litigation imposes burdens on those lacking financial and political resources and further drains valuable assets of time and energy. The courts further failed to meet the demands of land use and environmental conflict through the legal system’s inability to address multiple issues at one time, leaving waste of extensive resources from public funds to fund lengthy court proceedings. Moreover, resolutions found through alternatives to litigation might prove more durable and effective than if resolved in a court by a judge with little or no attachment to the dispute at hand, and limited expertise on the complex technical and scientific issues characteristic of environmental disputes. The court’s atmosphere often fosters antagonistic relationships between parties in land use and environmental disputes who often stand pitted against each other to fight for a particular ruling. The nature of decisions handed out to resolve conflits in land use and environmental areas, may impose grave consequences in a community or ecosystem,and are often highly controversial and emotional, miscommunication, lack of information and lack of understanding of the intricate scientific issues involved with the environment, time consuming, high costs, difficulty with using courts to resolve land use and environmental disputes In light of these difficulties, representatives of business, citizen groups, environmentalists, and local, state, and federal administrators have increasingly turned to alternative forms of dispute resolution like mediation to resolve disputes they would otherwise take to court. This research identified the possibilities of using alternative dispute resolution mechanism to improve conflict resolution in resolving land use planning and environmental disputes effectively.